2011
DOI: 10.1016/j.crohns.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of azathioprine on birth outcomes in women with inflammatory bowel disease (IBD)

Abstract: The use of AZA/6-MP during pregnancy in IBD women was not associated with an increased risk of preterm birth, LBW at term, neonatal adverse outcomes and congenital anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 20 publications
1
35
0
2
Order By: Relevance
“…66 Recently, in a study of 19 births exposed to AZA/MP and 74 controls, the use of AZA/MP was not associated with an increased risk of preterm birth, LBW at term, neonatal adverse outcomes or congenital anomalies. 67 Also reporting similar findings, the results from 215 pregnancies in 204 women who were a cohort of the CE-SAME study in France was published. Three groups of women were compared -women exposed to thiopurines, women receiving other drugs and women not receiving any medication.…”
supporting
confidence: 69%
“…66 Recently, in a study of 19 births exposed to AZA/MP and 74 controls, the use of AZA/MP was not associated with an increased risk of preterm birth, LBW at term, neonatal adverse outcomes or congenital anomalies. 67 Also reporting similar findings, the results from 215 pregnancies in 204 women who were a cohort of the CE-SAME study in France was published. Three groups of women were compared -women exposed to thiopurines, women receiving other drugs and women not receiving any medication.…”
supporting
confidence: 69%
“…small for gestational age, has also been reported [3]. Furthermore, the risk of Caesarean section being required is 1.5-9 times greater in women suffering from IBD [4].…”
Section: Introductionmentioning
confidence: 91%
“…Data were compared between the two groups. Results Females with pancolitis had a mean age of 25.1 years with a disease duration of 4 . None of the newborns in either group were detected to have any major congenital anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis, of fi ve larger studies assessing the birth outcomes of women with IBD exposed to thiopurines within three months of conception and / or during pregnancy, showed that thiopurine use was associated with preterm birth (odds ratio = 1.67; 95 % confi dence interval = 1.26 -2.20) but not birth defects ( 10 ). However, only two of the included studies accounted for disease activity by using hospital admissions as a marker of more severe disease ( 11,12 ). In addition, most studies were retrospective in design and relied on interviews and self-reporting for data collection, which is susceptible to recall bias.…”
mentioning
confidence: 96%